Steroid Hormone Secretion Over the Course of the Perimenopause: Findings From the Swiss Perimenopause Study - Grub, Jessica; Süss, Hannah; Willi, Jasmine; Ehlert, Ulrike (Frontiers in Global Women's Health, 2021)
Background: Perimenopause is characterized by a decline in the steroid hormones, estradiol, and progesterone. By contrast, the steroid hormone cortisol, a marker of the hypothalamic–pituitary–adrenal (HPA) axis, increases. Recent longitudinal studies reported fluctuations in steroid hormone levels during perimenopause, and even increases in estradiol levels. To understand these confounding results, it is necessary to conduct a longitudinal, highly standardized assessment of steroid hormone secretion patterns in perimenopausal women. Methods: This longitudinal study investigated 127 perimenopausal women aged 40–56 years for 13 months. Estradiol, progesterone, and cortisol were assessed using saliva samples, which were collected for two (during months 2 and 12 for estradiol and progesterone) or three (during months 2, 7, and 12 for cortisol) non-consecutive months over the course of the study. A total of 14 saliva samples per participant were analyzed to investigate the courses of estradiol and progesterone. Cortisol awakening response and fluctuations of cortisol throughout the day were measured using a total of 11 saliva samples per participant (on awakening, +30 min, +60 min, at 12:00 p.m., and before going to bed) for months 2, 7, and 12. Results: Multilevel analyses revealed variance in intercept and slope across participants for estradiol [intercept: SD = 5.16 (95% CI: 4.28, 6.21), slope: SD = 0.50 (95% CI: 0.39, 0.64)], progesterone [intercept: SD = 34.77 (95% CI: 25.55, 47.31), slope: SD = 4.17 (95% CI: 2.91, 5.99)], and cortisol (intercept: SD = 0.18 (95% CI: 0.14, 0.23), slope: SD = 0.02 (95% CI: 0.01, 0.02)]. Time predicted cortisol levels [b = −0.02, t(979) = −6.63, p < 0.0001]. Perimenopausal status (early vs. late) did not predict estradiol [b = −0.36, t(1608) = −0.84, p = 0.400], progesterone [b = −4.55, t(1723) = −0.87, p = 0.385], or cortisol [b = 0.01, t(1124) = 0.61, p = 0.542] scores over time. Discussion: Our results are consistent with previous findings emphasizing highly individual fluctuations of estradiol and progesterone levels during perimenopause. However, our findings do not suggest a continuous decline during the observed transition phase, implying relatively stable periods of fluctuating hormone levels. Furthermore, given the lack of significant group differences, it may not be necessary to differentiate between early and late perimenopause from the standpoint of hormonal progression.